Vier Karten zur physischen Geographie von El Salvador - Gierloff-Emden, Hans-Günter (ERDKUNDE, 1957)
The morphology of El Salvador, so far little known and scantily described, is depicted in four maps by the author, who travelled in the country in 1954-55. The landforms of the country are shown in a morphographic sketch map which is accompanied by a detailed geomorphological description. Furthermore, a regional subdivision of El Salvador on a geomorphological basis was attempted; this is shown on an additional map. A contour map and a map of the drainage basins are also enclosed. The purpose of this paper is to contribute to the knowledge of the physique of the Central American country, El Salvador, and by means of these maps to provide a basis for further work in regional geography.